Patterns of Care and Outcomes of Hypofractionated Chemoradiation Versus Conventionally Fractionated Chemoradiation for Glioblastoma in the Elderly Population. (February 2018) - Haque, Waqar; Verma, Vivek; Butler, Edward B.; Teh, Bin S.
Abstract : Purpose: This study evaluated practice patterns, outcomes, and predictors of survival for elderly patients with glioblastoma (GBM) receiving definitive chemoradiotherapy (CRT) with either hypofractionated radiotherapy or conventionally fractionated radiotherapy. Materials and Methods: The National Cancer Data Base was queried for patients age 65 years and above diagnosed with GBM between 2006 and 2012 that received definitive CRT with either hypofractionated radiotherapy (hCRT) or conventionally fractionated radiotherapy (cCRT). Patient, tumor, and treatment parameters were extracted. Statistics included Kaplan-Meier analysis to evaluate overall survival (OS) as well as Cox proportional hazards modeling to determine variables associated with OS. Propensity score matching was performed in order to assess groups in a balanced manner while reducing indication biases. Results: Altogether, 5126 patients met inclusion criteria; 126 (2.5%) underwent hCRT, while 5000 (97.5%) received cCRT. Temporal trends revealed that the use of hCRT is rising, especially in more recent years. Patients undergoing hCRT were older, with worse performance status, treated with biopsy only, and more likely to receive treatment at an academic facility. cCRT was associated with improved median OS (10.7 vs. 6.2 mo, P <0.001). This persisted in both Cox multivariate analysis (hazard ratio, 0.59; 95% confidence interval, 0.49-0.72; P =<0.001) and on propensity-matched analysis (median OS 8.7 vs. 6.2 mo; hazard ratio, 0.69; 95% confidence intervcal, 0.53-0.89; P =0.005). Conclusions: This is the first study to directly evaluate hCRT versus cCRT for patients with GBM. The use of hCRT is rising over time; practice patterns of hCRT administration are evaluated. Delivery of hCRT independently predicted for poorer OS. Prospective data is recommended to validate the findings herein.